EDUCATION FOR PHYSICAL EXERCISE IN THE PREVENTION OF CARDIOVASCULAR DISEASE: THE VALUE OF CHANGES IN LIFESTYLE. (Fiep Bulletin - online, 2016)
Aims: The decrease in daily physical activities and physical exercises performed by the population in general, can be clearly observed, contributing to the increase in chronic degenerative diseases and, consequently, to the increase in cardiovascular disease. The physical exercise is associated with a decreased incidence of cardiovascular events, together with a well balanced diet. Therefore, education, understanding and motivation of individuals to adherence to exercise programs and changes in lifestyle are important and can help in preventing these diseases. Methodology: Literature review by subject in MEDLINE (PUBMED), BIREME (LILACS) and SCIELO database, published from 2008 to 2014 and books published from 2005 to 2010. Objective: Highlight the importance of educating individuals to lifestyle change with physical exercise in the prevention of cardiovascular diseases. Conclusions: The improvement of eating habits and physical exercise have been considered effective at preventing cardiovascular disease and can aid in the treatment of these individuals, making them able to do their work with autonomy, self-awareness and self-discipline, thus gaining quality of life, health and general welfare. Adherence to lifestyle changes will only be won when understood and introjected by the individual, and also a joint action with health care professionals through education and awareness, aiming at reducing mortality and improving the quality of life and life expectancy.
Keywords: Education; Prevention; Exercise; Cardiovascular Diseases.